2017
DOI: 10.4236/ojmh.2017.74017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nitrogen and Phosphorus Dynamics on the Kinneret Phytoplankton: II: Chlorophyta, Cyanophyta, Diatoms and Peridinium

Abstract: Lake Kinneret long-term data of the epilimnetic concentrations (ppm) and loads (tones) of the total Nitrogen (TN), total Phosphorus (TP), total inorganic Nitrogen (TIN), total Dissolved Phosphorus (TDP), Phytoplankton groups' biomass, water level (WL) and Jordan River Discharge were analyzed. Previously collected data compiled aimed at an insight into the causative background for the modification of Phytoplankton community change. The study was carried out by searching for relations between algal groups' densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This paper is a tentative confirmation of the impact of climate change on nutrient dynamics and consequent modification of Phytoplankton composition. Likely, climate changes of temperature increase and decline in rainfall and water discharges caused the decline of Peridinium and Cyanobacteria enhancement [25][26][27][28][29]. It is suggested that rainfall and river discharge decline caused the reduction of nitrogen supply [29].…”
Section: Resultsmentioning
confidence: 99%
“…This paper is a tentative confirmation of the impact of climate change on nutrient dynamics and consequent modification of Phytoplankton composition. Likely, climate changes of temperature increase and decline in rainfall and water discharges caused the decline of Peridinium and Cyanobacteria enhancement [25][26][27][28][29]. It is suggested that rainfall and river discharge decline caused the reduction of nitrogen supply [29].…”
Section: Resultsmentioning
confidence: 99%
“…DOC, nitrogen, and phosphorus were important nutrient factors which could promote the growth of Ochrophyta [42]. In the wet season, module B, C, and E were dominated by Chlorophyta (Figures 3 and 8), which could be strongly driven by high temperature, high light, and high organic matter [43,92]. Like the overall microeukaryotic communities, most major modules in the dry season were closely correlated with nutrients, for example, high concentration of available nitrogen and SRP driven the growth of Cryptomonas and Ciliophora [33,93,94].…”
Section: Discussionmentioning
confidence: 99%